PENGARUH EVENT DAN KONTEN INSTAGRAM TERHADAP BRAND AWARENESS DAN DAMPAKNYA PADA MINAT MENABUNG DI ALLO BANK - Maro, Raissa Revanka; Prasetyawati, Yuliana Riana (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This study aims to determine the effect of events and Instagram content on brand awareness and its impact on interest in saving at Allo Bank, where Allo Bank has held the Allo Bank Festival event as well as the grand launching of Allo Bank. This research uses a quantitative approach with survey research methods. The research sample consisted of prospective Allo Bank customers who participated in the Allo Bank Festival event and actively used Instagram as one of the social media platforms. This research was conducted through the stages of pre-test, T-test, F-test, coefficient of determination test, and path test. The method used to analyse data is quantitative with descriptive research. After distributing questionnaires to 100 respondents, the results found that: (1) Events have a positive effect on brand awareness with a beta value of 0.505 and a probability value of sig. 0.000. (2) Instagram content has a positive effect on brand awareness with a value of 0.444 and a sig. probability value of 0.000. (3) Events have no influence on interest in saving because they have a significance value of 7.12. (4) Instagram content has an influence on interest in saving because it has a beta value of 0.508 with a sig value. 0.000. (5) Instagram content through brand awareness has a positive effect on interest in saving. (6) Brand awareness affects the interest in saving with a sig value. 0.000.